Characterization of Extracellular Chitinase from Bacterial Isolate 99 and Enterobacter sp. G-1 from Matsue City, Japan - MARIA ENDO MAHATA; ABDI DHARMA; IRSAN RYANTO; YOSE RIZAL (Indonesian Society for microbiology, 2008)
One hundred and twenty isolates of chitosanase producing bacteria were screened from water and soil from localies around Matsue city, Japan. In previous experiments, four isolates (isolates 96, 97, 99, and 100 strain ) were analyzed for their chitosanase characteristics, and one of the isolates (99) was detected as being both a chitosanase and a chitinase producer. Characteristics of the chitinase enzyme were analyzed in this study. Chitinase from bacterial isolate 99 showed higher activities compared to that Enterobacter sp. G-1 (isolated from water in Matsue city, Japan), the activity was 0.039 U/ml and the specific activity was 0.56 U/mg protein, while those from Enterobacter sp. G-1 were 0.029 U/ml and 0.48 U/mg protein respectively. Chitinase from isolate 99 was stable in a pH range between 4-7, while that from Enterobacter sp. G-1 was stable in pH range 3-7. Optimum pH of the chitinase produced by isolate 99 was 5 whereas the chitinase from Enterobacter sp. G-1 it was pH 7. Chitinase from isolate 99 was stable at temperature 20-60°C, while that from Enterobacter sp. G-1 at 20-50°C. Chitinase secreted by isolate 99 showed optimum temperature of 50°C while chitinase from Enterobacter sp. G-1 was optimal at 40°C. Several ions (Fe2+, Ba2+, Co2+) increased the activity of the enzyme from isolate 99 whereas Ca2+ and Co2+ increased activity of the Enterobacter sp. G-1 chitinase..